EFEKTIVITAS SISTEM INFORMASI PENGANGGARAN TERHADAP PENCAPAIAN KINERJA - Trisugiarto, Teguh (Universitas Jember, 2016)
The purpose of this study is to identify effectiveness implementation of performance-based budgeting system and performance achievements. The concept of budgeting is based on the logic models that find the relationship between inputs, processes, outputs and outcomes also customer oriented (external perspective). This study uses literature study and compare with other studied. From this studied, the results then compared with the provisions and the purpose of performance achievement. The result shows that the performance-based budgeting system can applied and support in achieving the vision and mission as well as the effect on performance. But the performance measurement only on budget absorption. Moreover there are inconsistencies when use performance indicators.